2017
DOI: 10.21303/2585-6847.2017.00470
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Acrylic Artificial Stone Properties

Abstract: The article is devoted to the research of the acrylic artificial stone properties, which has wide application in the production of furniture, in particular for the bathroom (sinks, baths), kitchens (sinks, countertops, bar counters, table tops for dining tables) and decorative interior elements (window sills, wall panels). In the Ukrainian market there are products of well-known world producers of acrylic artificial stone TM "Corian" (DuPont, USA), "Polystone" (China), LG Chem (South Korea), "Staron" and "Temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Andriievska and Marchuk [23] made an extensive comparison of the characteristics of this material from five different manufacturers. They subject samples of TM Tristone (South Korea) Bitto Dongguan (China), Corian ® (USA), Polystone (China) and LG Ni-macs (South Korea) to standard methods for the following parameters: density, water absorption, compressive strength, flexural strength, impact resistance, wear resistance, Mohs hardness and chemical resistance.…”
Section: Research Bibliographymentioning
confidence: 99%
“…Andriievska and Marchuk [23] made an extensive comparison of the characteristics of this material from five different manufacturers. They subject samples of TM Tristone (South Korea) Bitto Dongguan (China), Corian ® (USA), Polystone (China) and LG Ni-macs (South Korea) to standard methods for the following parameters: density, water absorption, compressive strength, flexural strength, impact resistance, wear resistance, Mohs hardness and chemical resistance.…”
Section: Research Bibliographymentioning
confidence: 99%
“…Andriievska and Marchuk [19] made an extensive comparison of the characteristics of this material from five different manufacturers. They subject samples of TM Tristone (South Korea) Bitto Dongguan (China), Corian ® (USA), Polystone (China) and LG Ni-macs (South Korea) to standard methods for the following parameters: density, water absorption, compressive strength, flexural strength, impact resistance, wear resistance, Mohs hardness and chemical resistance.…”
Section: Research Bibliographymentioning
confidence: 99%
“…At the same time, artificial cast stone is resistant to chemicals. It does not emit any gases at room temperature, as this material is made from 1/3 of polymethyl methacrylate (PMMA) and 2/3 of naturally occurring minerals that are not volatile or toxic to the environment [ 2 ]. Despite all the benefits of this material, manufacturers face the challenge of custom manufacturing.…”
Section: Introductionmentioning
confidence: 99%
“…No such published research has been found in the furniture industry (for the production of countertops and sinks, bathroom components and cabinet furniture facades). Due to the growing demand for artificial cast stone products in Lithuania, there is therefore a need to investigate the performance and mechanical properties of this material [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation